Embracing Generational Labels: An Analysis of Self-Identification and Political Partisanship - Andrew M. Lindner; Sophia Stelboum; Azizul Hakim (Socius, 2024)
Despite the popularity of generational labels like Boomers, Gen X, Millennials, and Gen Z in mass media, social scientists have debated their usefulness and accuracy in research. Consequently, little is known about the actual rate of self-identification with these generational labels in the U.S. population. This study investigated these labels as social identities and examined the extent of intragenerational variation in identification rates by birth year. Additionally, we explored the associations among political partisanship, demographic factors, and generational self-identification. Using logistic regression analyses of data from a nationally representative survey of 1,478 Americans, we find that a majority of respondents self-identify with a generational label, but individuals with birth years in the middle of the generational range exhibit much higher rates of self-identification. However, our analysis reveals little evidence for variation in generational self-identification based on party, race, or other demographic characteristics.